THE FIRST STEP IN STUDYING THE INFLUENCE OF GAMMA RADIATION ON MAGNETIC PROPERTIES OF CoFe₂O₄ NANO-PARTICLES - NGUYEN , MONG GIAO; NGUYEN , THI AI THU; NGUYEN , LAM THU TRANG (Nuclear Science and Technology, 2011)
The influence of radiation on magnetic material has been investigated in some researches and the results proved the magnetic properties of hard magnetic are unchangeable under radiating effect. Our works are aimed at studying the influence of gamma radiation on the nano-size magnetic materials. The gamma radiation with 1332keV and 1174keV energy was emitted on CoFe2O4 nano-particles with various doses. The comparison of properties of the materials before and after emitting was analyzed by hysteresis loop VSM.The change recorded to CoFe2O4 nano-particles reduced obviously in after radiating. This result enables to be a new discovery which could be uncovering the other interested properties of nano magnetic materials.